2017
DOI: 10.1080/08927014.2016.1269893
|View full text |Cite
|
Sign up to set email alerts
|

Epilithic and endolithic microorganisms and deterioration on stone church facades subject to urban pollution in a sub-tropical climate

Abstract: Weathering of two church facades in Rio de Janeiro was caused substantially by salts, mainly halite and gypsum, detected by SEM and chemical analyses, which cause physical stresses by deposition within the rock. Biofilm populations, determined by SEM and as operational taxonomic units (OTUs), degraded stone by penetration, solubilization and redeposition of minerals on their surfaces. Endolithic cyanobacteria were associated with gypsum deposits. Microbiomes were typical for high-stress environments, high salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 65 publications
1
23
0
2
Order By: Relevance
“…EDS suggests that the crystalline formations on the mummy's surface are likely crystals of potassium sulfate (K 2 SO 4 ), also known as the mineral arcanite. This mineral is present in the efflorescences that arise during the decay of many building materials (Vázquez et al ., ; Gaylarde et al ., ). In the present case, the substance did not appear as a homogenous encrustation, but as small individual crystals embedded into the skin over the whole body, a phenomenon of which we could find no similar reports in the literature.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…EDS suggests that the crystalline formations on the mummy's surface are likely crystals of potassium sulfate (K 2 SO 4 ), also known as the mineral arcanite. This mineral is present in the efflorescences that arise during the decay of many building materials (Vázquez et al ., ; Gaylarde et al ., ). In the present case, the substance did not appear as a homogenous encrustation, but as small individual crystals embedded into the skin over the whole body, a phenomenon of which we could find no similar reports in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…Whether any of these, or any of the other identified organisms deposit K 2 SO 4 remains unknown, however. To our knowledge, arcanite deposition has been described in the literature only in relation to biofilm rock weathering (Gaylarde et al ., ). This hypothesis is plausible, but other, more detailed analyses need to be done to validate it.…”
Section: Discussionmentioning
confidence: 97%
“…These harsh conditions can regularly and significantly vary over time, meaning that stone‐dwelling microbes must adapt to potentially polar ranges of these stressors on stone surfaces (Gorbushina, ). Despite this obstacle, diverse microbial communities persist on stone surfaces around the world, particularly in humid environments (Urzi and Realini, ; Ortega‐Morales et al ., ; Gaylarde et al, , b). Primary functions of stone biofilms are directly involved in community survival and include those associated with water retention, UV light protection, stone adhesion, and even capture of trace organic material from the environment (Kemmling et al ., ; Gorbushina, ).…”
Section: Introductionmentioning
confidence: 98%
“…We used both high‐throughput amplicon (targeting the 16S rRNA gene) and whole metagenome shotgun sequencing on stone ruins from three distinct climates in Tunisia and Algeria to achieve our objectives. Although climate has been shown to have an impact on stone microbes of the Mediterranean basin (Macedo et al ., ), most previous research on the microbiome of stone structures of Europe, North America, and South America has instead focused on stone geochemistry as drivers of diversity and functional variation (Cockell et al ., ; Krakova et al ., ; Chimienti et al ., ; Brewer and Fierer, ; Gaylarde et al ., ,b). In this study, we aimed to determine what aspects of the climate, including precipitation, temperature and others, were associated with specific microbial community variation, particularly in representation of Actinobacteria and Cyanobacteria colonizers.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of urban soils from the street green belts of the city of Chicago, USA, revealed that soils along a one‐way street showed higher Shannon and phylogenetic diversities than other soils, including those along a two‐way street, a feature that could be correlated with soil pH, moisture and texture (Wang et al ., ). We believe that the microorganisms living in the street, in street gutters and on pedestrian surfaces may present specific surface‐associated diversity, such as the ones identified on concrete (Domingo et al ., ; Li et al ., ; Gomez‐Alvarez et al ., ; Jiang et al ., ; Cayford et al ., ; Cowle et al ., ; Li et al ., ) or buildings and monuments (Ragon et al ., ; Chimienti et al ., ; Gaylarde et al ., ; Adamiak et al ., ; Dyda et al ., ).…”
Section: Introductionmentioning
confidence: 99%